Numerical Modeling of Turbulent Bottom Boundary Layer over Rough Bed under Irregular Waves - Taufiqur Rachman; Suntoyo Suntoyo; Kriyo Sambodho; Haryo Dwito Armono; Eko Yusroni (IPTEK The Journal for Technology and Science, 2011)
A numerical model of turbulent bottom boundary layer over rough bed under irregular waves is reviewed. The turbulence model is based upon Shear Stress Transport (SST) k- model. The non-linear governing equations of the boundary layer for each turbulence models were solved by using a Crank-Nicolson type implicit finite-difference scheme. Typical the main velocity distribution, turbulence kinetic energy and time series of the bottom shear stress are presented. These results are shown to be in generally good agreement with experimental result. The roughness effects in the properties of turbulent bottom boundary layer for irregular waves are also presented with several values of the roughness parameter (am/ks) from am/ks=5 to am/ks=3122. The roughness effect tends to decrease the main velocity distribution and to increase the turbulent kinetic energy in the inner boundary layer, whereas in the outer boundary layer, the roughness alters the mean velocity distribution and the kinetic energy turbulent is relatively unaffected. The effect of bed roughness on the bottom shear stress under irregular waves is found that the higher roughness elements increase the magnitude of bottom shear stress along wave cycle. And further, the bottom shear stress under irregular waves is examined with the existing calculation method and the newly proposed method.